United States natural gas prices to 2015 - Michot Foss, M (Oxford Institute for Energy Studies, 2007)
For 2005, total United States natural gas consumption as reported by the US Energy Information Administration (USEIA) was just below 22 Tcf, which was about 1 Tcf less than the historic high of 23 Tcf reached in 2000. At roughly 19 Tcf, the total figure for marketed production reported by USEIA was lower than the recent high of 20.6 Tcf reached in 2001 and substantially below the all-time high of 22.6 Tcf reached in 1973. For 2006, consumption will register slightly lower and production slightly higher, continuing the essentially flat to slightly declining market conditions that have prevailed since the mid- 1990s. A perennial "gap" between domestic production and demand became a feature of the US natural gas marketplace in 1988. After jumping a new hurdle of 2.7 Tcf in 1995, the supply-demand gap has generally ranged between 2 and 3.2 Tcf every year since then, except for 2000 when it achieved its widest point, reflecting a tightening of the US natural gas balance that was ultimately expressed in a sharp spike in prices set at Henry Hub in Erath, Louisiana, the main US (and North American) trading point. A narrowing in the supply-demand gap is estimated for 2006, a reflection of softer fundamentals and a precursor to a widely expected correction in prices during 2007.